Impact of previous abdominal surgery on the outcome of fundoplication for medically refractory gastroesophageal reflux disease in children and young adults - Steffens, Franziska; Dahlheim, Marcus; Günther, Patrick; Mehrabi, Arianeb; Vuille-dit-Bille, Raphael Nicolas; Fetzner, Ulrich Klaus; Gerdes, Berthold; Frongia, Giovanni (European surgery, 2023)
Fundoplication (FP) is a well-established surgical treatment for gastroesophageal reflux disease (GERD) refractory to medical therapy in children and young adults. During FP, previous abdominal surgery (PAS) can impair the patient’s outcome by causing technical difficulties and increasing intra- and postoperative complication rates.